Stakeholder perspectives on objectives-oriented evaluation of digital twin-based learning for industrial maintenance-troubleshooting: A qualitative evaluative study - Erik Sudharta; Welly Kuswanto; Rahmatul Irfan; Septian Rahman Hakim (Jurnal Pendidikan Vokasi, 2025)
Digital twin-based learning is increasingly relevant in vocational technology education because it enables students to observe machine behavior, simulate industrial faults, and practice maintenance-troubleshooting in a safe and repeatable environment. However, its educational effectiveness cannot be judged solely by technological sophistication or visual realism. This study examines stakeholder perspectives on an objectives-oriented evaluation of digital twin-based learning for industrial maintenance-troubleshooting competence. Grounded in objectives-oriented evaluation, competence-based assessment, stakeholder-informed interpretation, and curriculum alignment, the study employed a qualitative evaluative design involving students, instructors, laboratory technicians, program managers, alumni, and industry representatives. Data were collected through interviews, focus group discussions, observations, document analysis, and digital learning-log analysis. The findings reveal four interrelated evaluation dimensions: objective clarity, learning alignment, assessment quality, and stakeholder usefulness. Digital twin-based learning was considered educationally meaningful when learning outcomes were translated into observable performance indicators, authentic industrial scenarios were validated by stakeholders, and students engaged in progressive diagnostic tasks supported by process-based assessment. Stakeholders also identified several implementation challenges, including instructor readiness, platform reliability, cognitive overload, limited sensory realism, and fragmented assessment practices. This study contributes a stakeholder-informed evaluative framework for digital twin-based learning and provides practical guidance for strengthening curriculum alignment, assessment quality, instructor preparation, and continuous improvement in vocational technology education.